2018
DOI: 10.1111/cas.13576
|View full text |Cite
|
Sign up to set email alerts
|

Development of a vaccine based on bacteria‐mimicking tumor cells coated with novel engineered toll‐like receptor 2 ligands

Abstract: For a successful tumor vaccine, it is necessary to develop effective immuno‐adjuvants and identify specific tumor antigens. Tumor cells obtained from surgical or biopsy tissues are a good source of tumor antigens but, unlike bacteria, they do not induce strong immune responses. Here, we designed 2 novel lipopeptides that coat tumor cell surfaces and mimic bacterial components. Tumor cells coated with these lipopeptides (called bacteria‐mimicking tumor cells [BMTC]) were prepared and their efficacy as a tumor v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 56 publications
(120 reference statements)
0
3
0
Order By: Relevance
“…Thus, the conjugation of Pam 3 CSK 4 to peptide vaccines improved their anti-cancer activity in preclinical models [ 120 ], and a vaccine composed of a synthetic TLR2 ligand (called Amplivant ® ) conjugated to HPV16 E6 long peptides is currently undergoing a phase I clinical trial in patients with HPV16 positive tumors or premalignant lesions (NCT02821494). Although other vaccines exploiting TLR2 agonists as adjuvants have been recently tested in different preclinical models of solid tumors, clinical data on their safety and effectiveness have not been provided so far [ 121 , 122 ], in contrast to agonists of other TLRs that are extensively tested in the clinic [ 123 ]. Actually, TLR2 is activated by two poly-TLR agonists currently used or tested in cancer treatment, i.e., a Food and Drug Administration-approved live attenuated Mycobacterium bovis preparation of bacillus of the Calmette–Guerin strain and CADI-05, a polyantigenic vaccine containing heat-killed Mycobacterium indicus pranii currently undergoing clinical investigation.…”
Section: Tlr2-targeted Anti-cancer Therapymentioning
confidence: 99%
“…Thus, the conjugation of Pam 3 CSK 4 to peptide vaccines improved their anti-cancer activity in preclinical models [ 120 ], and a vaccine composed of a synthetic TLR2 ligand (called Amplivant ® ) conjugated to HPV16 E6 long peptides is currently undergoing a phase I clinical trial in patients with HPV16 positive tumors or premalignant lesions (NCT02821494). Although other vaccines exploiting TLR2 agonists as adjuvants have been recently tested in different preclinical models of solid tumors, clinical data on their safety and effectiveness have not been provided so far [ 121 , 122 ], in contrast to agonists of other TLRs that are extensively tested in the clinic [ 123 ]. Actually, TLR2 is activated by two poly-TLR agonists currently used or tested in cancer treatment, i.e., a Food and Drug Administration-approved live attenuated Mycobacterium bovis preparation of bacillus of the Calmette–Guerin strain and CADI-05, a polyantigenic vaccine containing heat-killed Mycobacterium indicus pranii currently undergoing clinical investigation.…”
Section: Tlr2-targeted Anti-cancer Therapymentioning
confidence: 99%
“…Activation of DCBUT by P2CSR11 induces less inflammatory inducer/interferon. P2CSR11 is a strong candidate antigen‐specific immunoadjuvant 132 …”
Section: Peptides With Different Functionsmentioning
confidence: 99%
“…Wu et al found that lipo-OVA (Ovalbumin fused with the TLR2 agonist, the lipid part of the bacteria) showed a strong anti-tumor effect by activating BMDCs maturation, promoting cross-presentation of tumor antigen, inducing CTL responses, increasing the numbers of CD8+ T cells (Wu et al, 2016). A vaccine comprising bacteria-mimicking tumor cells (BMTC) and P2CSR11/P2CSK11 (TLR2 ligand) promoted antitumor immunity by stimulating DCs and enhancing antigen presentation (Akazawa et al, 2018).…”
Section: Tlr2mentioning
confidence: 99%